CURRENT STATE OF SMALL BUSINESS CREDITING AND ITS ROLE IN THE DEVELOPMENT OF THE NATIONAL ECONOMY - Zhavoronok , A.V. (The actual problems of regional economy development, 2022)
Nowadays, the state and financial and credit institutions have begun to pay more attention to solving the problems of small business and the impact of state influence on the formation of this business has become more noticeable. The urgency of this topic is determined by the need to solve a significant list of problems and eliminate obstacles to obtaining a bank loan to ensure the normal level of their business. Creating a system of effective, mutually beneficial relations between commercial banks and small businesses in terms of financial and credit security should become the main norm of a civilized domestic market economy. The purpose of the article is to develop ways to improve the market for small business lending based on the latest banking technologies, as well as to identify and implement in the lending process of domestic commercial banks proposals for its activation and determine its role in the national economy. To achieve this goal, general scientific and specific research methods were used: descriptive, statistical, structural, monographic methods, as well as analytical methods. According to the study, today the problems in the interaction of small firms and banks hinder the effective cooperation of economic agents under consideration, and lead to a "vicious circle" in which the lack of development of the small business sector and its inefficiency leads to reluctance of banks to lend to small businesses. high credit risks. This, in turn, does not allow the small business sector to increase the volume of loans and obtain the necessary financial resources for development, which exacerbates these problems. As a result, the barrier between banks and small businesses continues to grow, as evidenced by a decrease in lending to small businesses, an increase in bad debts of banks, an increase in the number of bankruptcies in small businesses and more. At the same time, there is a growing mutual empathy between banks and the World Bank. Banks consider working with small firms as a hassle and, as a rule, which creates a lot of problems in the form of non-repayment of credit or problem debt. It is much easier and more efficient for a bank to provide credit to one large enterprise than to serve several hundred small ones. The scientific novelty is to identify the main problems of sustainable development of the small and business lending market in Ukraine and the development and practical implementation of their improvement through the prism of improving internal lending mechanisms and institutional conditions for small business.